Protocol for a Phase 2 randomized controlled patient-assessor blinded study: efficacy and safety of combined cortical and cerebellar dual-target transcranial magnetic stimulation for the treatment of essential tremor - Xu, Jing; Cao, Na; Qu, Yan; Shang, Suhang; Liu, Xincheng; Wang, Xuexin; Hu, Fangfang; Bai, Xuerong; Qu, Qiumin; Zhang, Meng; Cao, Hongmei (Frontiers in Neurology, 2025)
BackgroundEssential tremor (ET) is the most common neurological movement disorder with few treatments and limited therapeutic efficacy, research into noninvasive and effective treatments is critical. Abnormal cerebello-thalamo-cortical (CTC) loop function are thought to be significant pathogenic causes of ET, with the cerebellum and cortex are common targets for ET treatment. In recent years, transcranial magnetic stimulation (TMS) has been recognized as a promising brain research technique owing to its noninvasive nature and safety. In this study, we will use left M1 cortex continuous theta-burst stimulation (cTBS) combined with right cerebellar hemisphere 1 Hz repetitive transcranial magnetic stimulation (rTMS) dual-target stimulation to explore the Safety, feasibility and efficiency of this dual-target stimulation mode, and the mechanism of its therapeutic effect.MethodsTwenty-four patients with ET will be randomly assigned to three groups: dual-target stimulation, single-target stimulation, or sham stimulation. The single-target stimulation group will receive stimulation of the right cerebellar hemisphere for 10 days, whereas the dual-target stimulation group will be given stimulation of both the left M1 cortex and the right cerebellar hemisphere. The sham stimulation group will be given sham stimulation for 10 days. Tremor will be assessed using both the subjective The Essential Tremor Rating Assessment Scale (TETRAS) and objective accelerometer-based tremor analysis. at baseline (before stimulation), after the first, fifth, tenth days of treatment (D1, 5, 10), 24 h after 10 days of treatment (D10-24 h), and 1, 2, 3, and 4 weeks after stimulation (W1, 2, 3, 4).DiscussionThis is a Phase 2 randomized, controlled, patient-assessor blinded clinical trial. The goal of this study is to investigate the Safety, feasibility and efficiency of TMS for the treatment of ET.